A Global Perspective on Infection Control Measures for Healthcare Workers: A Systematic Review - Alshahrani, Ibraheem hadi; Alshahrani , Adel Mohammed Abdullah; Almansour, Saleh mohammed Hussain; Alsalem, Ali Hamad Amer; Althaiban, Abdullah Hamad; Al-Bishi, Yousef Mohammed Dhafer; Al Baataj, Mohammad Misfer Saleh; Bakri, Ali Yahya Ibrahim; Nazra, Rooa Adel Yousef; Alsweidan, Saleh Hussein (Journal of Ecohumanism, 2024)
Infection control measures are essential to safeguarding healthcare workers (HCWs) and preventing healthcare-associated infections (HAIs) worldwide. This systematic review examines the global implementation of infection control strategies, their effectiveness, and the disparities between high-income countries and low- and middle-income countries (LMICs). A comprehensive search was conducted across multiple databases, focusing on studies published since 2016 that evaluated infection control practices, including hand hygiene, personal protective equipment (PPE), vaccination, environmental cleaning, and waste management. Findings reveal significant variation in compliance and outcomes, with LMICs facing challenges such as resource shortages, inadequate training, and organizational deficiencies. Conversely, high-income countries demonstrate better adherence to infection control protocols, supported by advanced technologies and robust policies. Despite these differences, common barriers such as HCW burnout and vaccine hesitancy persist globally. The review underscores the need for equitable access to resources, international collaboration, and the integration of innovative technologies to enhance infection prevention measures. Addressing these disparities is critical to protecting HCWs, improving patient safety, and achieving global health equity.